2021
DOI: 10.1136/bmj.n1105
|View full text |Cite
|
Sign up to set email alerts
|

How to reposition the nursing profession for a post-covid age

Abstract: The effectiveness of healthcare is inextricably linked to the state of the nursing profession. The second report of the Independent Panel for Pandemic Preparedness and Response said, "The world was not prepared, and must do better," arguing that "the covid-19 pandemic must be a catalyst for fundamental and systemic change in preparedness for future such events, from the local community right through to the highest international levels." 1 Frailties in healthcare systems, exposed by the covid-19 pandemic, reinf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 16 publications
0
15
0
2
Order By: Relevance
“…Whereas 81% (230/283) of the respondents were female nurses while 19% (53/283) were males, the number of male nurses is very low as compared to female nurses around the globe. Since globally there are 9 out of 10 nurses are females ( Catton & Iro, 2021 ). The sample distribution regarding age level is as follows: 145 respondents (51%) were 25 to 30 years old; 75 respondents (27%) were 31 to 35 years old; 54 respondents (19%) were 36 to 40 years old; 9 respondents (3%) were 40 and above years old (see Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Whereas 81% (230/283) of the respondents were female nurses while 19% (53/283) were males, the number of male nurses is very low as compared to female nurses around the globe. Since globally there are 9 out of 10 nurses are females ( Catton & Iro, 2021 ). The sample distribution regarding age level is as follows: 145 respondents (51%) were 25 to 30 years old; 75 respondents (27%) were 31 to 35 years old; 54 respondents (19%) were 36 to 40 years old; 9 respondents (3%) were 40 and above years old (see Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Accordingly, a recent scoping review reported that nurses will be under an increased risk for stress, burnout, and depression during the pandemic, where younger female nurses, with less clinical experience, are more vulnerable to adverse mental health outcomes [ 37 ]. Catton and Iro [ 38 ], nurses in WHO and the International Council of Nurses (ICN), recently called for an investment in the augmentation of the nursing profession since the availability of adequate nursing staff can reduce inpatient admissions and hospital stays [ 39 ], a dire situation that most countries are currently facing.…”
Section: Discussionmentioning
confidence: 99%
“…However, society itself has responded positively to the visibility of front‐line nurses and their practice, which has increased the recruitment of nurses with many countries across the world (Garrett et al., 2021), although the African continent is an exception. Additionally, Catton and Iro (2021) recognise that from the ICN perspective and as a conservative estimate, approximately 115,000 nurses died during the pandemic and many nurses are burnt out as a result of pandemic working conditions with rates of ‘intention to leave’, in the past year, doubling to 20%–30% across its membership.…”
Section: Competing Investment Priorities?mentioning
confidence: 99%